2004
DOI: 10.1677/joe.0.1800357
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and diabetes in transgenic mice expressing proSAAS

Abstract: ProSAAS is a neuroendocrine peptide precursor that potently inhibits prohormone convertase 1 in vitro. To explore the function of proSAAS and its derived peptides, transgenic mice were created which express proSAAS using the beta-actin promoter. The body weight of transgenic mice was normal until approximately 10-12 weeks, and then increased 30-50% over wild-type littermates. Adult transgenic mice had a fat mass approximately twice that of wild-type mice, and fasting blood glucose levels were slightly elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 48 publications
4
69
0
Order By: Relevance
“…However, the finding that a cell line expressing low levels of proSAAS (line 7) is not affected to the same degree as lines expressing relatively high amounts of proSAAS (lines 5 and 41) implies that proSAAS is not very potent in vivo. These results are similar to those observed for proSAAS-expressing transgenic mice; mice with a twofold increase in the level of proSAAS do not show significant defects in the levels of processed neuropeptides (Wei et al 2004). Previous studies have established that the key peptide processing enzymes have pH optima in the acidic 5-6 range (Fricker and Snyder 1982;Eipper et al 1991;Greene et al 1992;Seidah and Chretien 1998a,b;Zhou et al 1999).…”
Section: Discussionsupporting
confidence: 83%
“…However, the finding that a cell line expressing low levels of proSAAS (line 7) is not affected to the same degree as lines expressing relatively high amounts of proSAAS (lines 5 and 41) implies that proSAAS is not very potent in vivo. These results are similar to those observed for proSAAS-expressing transgenic mice; mice with a twofold increase in the level of proSAAS do not show significant defects in the levels of processed neuropeptides (Wei et al 2004). Previous studies have established that the key peptide processing enzymes have pH optima in the acidic 5-6 range (Fricker and Snyder 1982;Eipper et al 1991;Greene et al 1992;Seidah and Chretien 1998a,b;Zhou et al 1999).…”
Section: Discussionsupporting
confidence: 83%
“…supports a role for the BigLEN-GPR171 system in regulating these functions. This idea is supported by the finding that third ventricular injections of antibodies to BigLEN affect food intake in mice that can be augmented by GPR171 knockdown and by previous studies which found that overexpression or deletion of proSAAS produces alterations in body weight (10,11). The identification of GPR171 as the receptor for BigLEN provides insights into these mechanisms but also may provide a target for therapeutic modulation of food intake and metabolism.…”
Section: Knockdown Of Gpr171 Affects Feeding Behaviors and Metabolism Inmentioning
confidence: 77%
“…36,39 However, the pituitary is sufficiently rich in neuropeptides that affinity purification is not necessary for this tissue. 40 Recently, it was reported that neuropeptides could be detected in extracts of hypothalami from animals killed by focused microwave irradiation; 41 hence it should be possible to apply the technique used in the present study to the analysis of brain peptides.…”
Section: Discussionmentioning
confidence: 93%